ROAD TRAFFIC ACCIDENTS IN INDIA: AN OVERVIEW - Shantajit, Thokchom; Kumar, Chirom Ranjeev; Zahiruddin, Quazi Syed (International Journal of Clinical and Biomedical Research, 2018)
Road traffic accidents claim over a million lives every year in the world. As per World Health Organization (WHO) it is one of the leading cause of death. India, being a rapidly developing country with expanding economy has its own issues as regarding road traffic accidents due to rapid proliferation of motorization. Road traffic accidents causes enormous morbidity and mortality and at the same time, the toll on the economy of the country as a result of it is quite heavy. Road traffic accident is a result of an interaction among different factors which include the environment, vehicle and the human being. Traditionally it is considered that road traffic accidents are accidents which are unpredictable, inevitable and not preventable. But road traffic accidents are indeed predictable and preventable in majority of the cases. This require the knowledge of factors contributing and leading to road traffic accidents. There are certain preventive measures which if adopted can lead to decrease in morbidity and mortality resulting from RTA. Hence, it is the responsibility of all to contribute in reducing road traffic accidents. Keywords: Road traffic accidents; Road traffic injuries; Roads in India; Road safety; Vehicular registration.